Defining Menstrual Literacy With the Aim of Evaluating Mobile Menstrual Tracking Applications. Issue 12 (December 2019) - Eschler, Jordan; Menking, Amanda; Fox, Sarah; Backonja, Uba
Abstract : For the estimated 75 million people in the United States who menstruate, understanding menstrual health as a critical "vital sign" is an important aspect of managing personal health. Unsurprisingly, in the past decade, menstrual tracking applications have become increasingly popular, with more than 300 applications available for download and an estimated 200 million downloads worldwide. This study had two purposes. The first was to formulate a definition for menstrual literacy —a baseline of knowledge and skills for understanding anatomical and biological facts of menstruation, caring for the menstruating body, and completing menstrual care tasks—by building on prior work about health literacy and by conducting content analysis of eight Web sites containing information about menstruation. The second was to evaluate a maximum variation sample of 17 menstrual tracking applications; here, features and functions related to the concepts about menstrual literacy identified in a content analysis were compared. These applications had insufficient support for facilitating menstrual literacy, especially for teen and perimenopausal users. The article discusses these disconnects and subsequent design opportunities for menstrual tracking applications to facilitate more robust support of menstrual literacy and overall health of people who menstruate.